2022
DOI: 10.1093/europace/euac211
|View full text |Cite
|
Sign up to set email alerts
|

Findings from repeat ablation using high-density mapping after pulmonary vein isolation with pulsed field ablation

Abstract: Aims Pulsed-field ablation (PFA) can offer a novel perspective for atrial fibrillation (AF) ablation. We aimed to characterize the incidence of pulmonary vein (PV) reconnection, types of recurrent atrial tachyarrhythmia (ATa) and lesion quality after PFA-guided PV isolation (PVI). Methods and results Patients undergoing second ablation for recurrent ATa following the initial PVI using the pentaspline PFA catheter were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 20 publications
3
47
1
Order By: Relevance
“…If confirmed in larger studies, this may represent a sign of a recurrence shift after PVI, with arrhythmia recurrence less related to PV reconnection and more related to man-made tachycardias, as suggested by our observation of a corridor of slow conduction in the posterior wall between the PV ostia after PFA ablation. 24…”
Section: Limitationsmentioning
confidence: 99%
“…If confirmed in larger studies, this may represent a sign of a recurrence shift after PVI, with arrhythmia recurrence less related to PV reconnection and more related to man-made tachycardias, as suggested by our observation of a corridor of slow conduction in the posterior wall between the PV ostia after PFA ablation. 24…”
Section: Limitationsmentioning
confidence: 99%
“…Our data demonstrating 3D-mapping-based larger antral lesions in the PFA cohort are in line with the previous findings and provide an explanation for the higher number of postablation atrial tachycardia in the PFA group. 13 We believe that the higher occurrence of postablation atrial tachyarrhythmias in this group is dependent on lesion-size rather than on the energy source itself.…”
Section: Discussionmentioning
confidence: 74%
“…What is known from previous studies is that a wide antral approach is more effective than ostial PVI in achieving freedom from atrial tachyarrhythmia recurrence at long‐term follow‐up 12 . However, as recently described by Tohoku et al, 13 PVI based on the pentaspline PFA catheter can be associated with postablation macro‐reentrant atrial tachycardia with a critical isthmus at the LA posterior wall. Our data demonstrating 3D‐mapping‐based larger antral lesions in the PFA cohort are in line with the previous findings and provide an explanation for the higher number of postablation atrial tachycardia in the PFA group 13 .…”
Section: Discussionmentioning
confidence: 97%
“… 26) Others confirmed the advantage of the novel waveform in patients who necessitated redo procedure after initial PFA-PVI: solely 9.1% of PV showed reconnection. 85) Additional works reported that the chronic antral lesion size created with PFA (pentaspline catheter) persists over time 72) and is comparable to the ones with RF, cryo- or laserballoon ablations. 86) Interestingly, in an MRI study, most of the large late gadolinium enhancement (LGE) lesions acutely induced by PFA disappeared over time, whereas those persisted after RF- or cryoablation, e.g., caused chronic fibrosis.…”
Section: Pulsed Field Ablation: Efficacy Safety and Fields Of Applica...mentioning
confidence: 97%